2003
DOI: 10.1021/jf0204809
|View full text |Cite
|
Sign up to set email alerts
|

Fatty Acid Distribution in Muscle, Liver, and Gonads of Rays (Dasyatis marmorata, Rhinobatos cemiculus, and Rhinoptera marginata) from the East Tropical Atlantic Ocean

Abstract: If a great number of rays are fished in the Tropical East Atlantic Ocean for their caudal fins, only a small amount of ray flesh is processed. Among them, three species of rays, Dasyatis marmorata, Rhinobatos cemiculus, and Rhinoptera marginata, from the Mauritanian coast have been investigated for the fatty acid composition of their lipids. Gas chromatography and gas chromatography-mass spectrometry allowed identification of 50 molecules from muscles, livers, and gonads of these fishes. Principal component an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
25
3
3

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 15 publications
9
25
3
3
Order By: Relevance
“…47 Similarly, 48 reported that oil extracted from the liver of ray fish Himantura bleekeri confirmed that the liver is relatively rich in lipids which implies 54 % of the fresh matter containing lipids. In accordance with previous studies, lipid content of other elasmo branch livers was ranging from 23 to 67 % 49, [50][51][52][53] reported that the lipid content of liver of Dasyatis brevis and Gymnura marmorata as 50.80 % and 51.50 % of the total lipids respectively. The lipid content of seawater species ranged from 1.01 ± 0.12 -12.4 ± 0.45 % for blue fish to sea bream 54,55 demonstrated that the total lipid content was about 32 mg/g (w/v) in wild sea bass and 37.5 mg/g in farmed sea bass.…”
Section: Discussionsupporting
confidence: 89%
“…47 Similarly, 48 reported that oil extracted from the liver of ray fish Himantura bleekeri confirmed that the liver is relatively rich in lipids which implies 54 % of the fresh matter containing lipids. In accordance with previous studies, lipid content of other elasmo branch livers was ranging from 23 to 67 % 49, [50][51][52][53] reported that the lipid content of liver of Dasyatis brevis and Gymnura marmorata as 50.80 % and 51.50 % of the total lipids respectively. The lipid content of seawater species ranged from 1.01 ± 0.12 -12.4 ± 0.45 % for blue fish to sea bream 54,55 demonstrated that the total lipid content was about 32 mg/g (w/v) in wild sea bass and 37.5 mg/g in farmed sea bass.…”
Section: Discussionsupporting
confidence: 89%
“…sarsi (Sato et al, 2001) : acides 7E,13E-20:2 ; 7E,13E,17Z-20:3 ; 9E,15E,19Z-22:3 ; 4Z,9E,15E,19Z-22:4 (figure 9). Les AG non maloniques 20:2 Δ7,13 ; 20:2 Δ7,15 ; 22:2 Δ7,13 ; 22:2 Δ7,13 et le nouveau 22:2 Δ6,14 étaient présents dans les lipides totaux de divers organes trois raies de l'Atlantique tropical (Ould El Kebir et al, 2003, 2007. Ces AG non maloniques n'avaient jamais été signalés chez les poissons et les raies, bien que ces dernières se nourrissent largement de mollusques et de crustacés benthiques (Barnathan, 2009).…”
Section: Ag Non Maloniques D'autres Organismesunclassified
“…Gas Chromatography-Mass Spectrometry Fatty acids were identified by mass spectrometry (MS) of the respective FAME and pyrrolidide and compared to previously published results [12,13]. The GC/MS data for the pyrrolidide derivatives were obtained to confirm the structures and to determine double bond positions.…”
Section: Preparation and Gas Chromatography Analysis Of Fa Methyl Estersmentioning
confidence: 99%